Cymbopogon winterianus, Neurolaena lobata, and Ruta chalepensis—Recurring Herbal Remedies in Guatemalan Maya Q’eqchi’ Homegardens - Thiel, Amanda M.; Quinlan, Marsha B. (Ethnobiology Letters, 2022)
Abstract We report on the top three ethnopharmacological herbs growing among a lowland Guatemalan Q’eqchi’ community’s homegardens. In a gardening culture characterized by pragmatic species distribution and sharing, these few herbaceous species recur in multiple households’ dooryard gardens. Our aim in reporting on the most predominant ethnobotanical herbs gardened in a Maya Q’eqchi’ village’s dooryards is to valorize the capacities of local pharmacological traditions. Thirty-one walking homegarden interviews and participant-observation inform this research with village residents. Té de limón (Cymbopogon winterianus, for cough, fever), Qa’mank/Tres punta (Neurolaena lobata, for diabetes, fever, headache, gastrointestinal ills, evil eye), and Ruda (Ruta chalepensis, for children’s vomiting, weepiness, evil eye) are the prevalent non-woody Q’eqchi’ homegarden herbs here. Regional ethnomedical and extant pharmacology research mutually support the efficacy and continued practicality of these Q’eqchi’ plant uses. Ethnopharmacological research of Maya Q’eqchi’ medicinals documents local knowledge for conservation and calls for their cultural and biomedical respect as prominent, accessible, therapeutic species. Resumen Reportamos sobre las tres principales hierbas etnofarmacológicas cultivadas en los huertos familiares de una comunidad Q’eqchi’ guatemalteca de tierras bajas. En una cultura de jardinería caracterizada por la distribución pragmática de especies y el intercambio, algunas especies herbáceas se repiten en los huertos familiares de múltiples hogares. Nuestro objetivo al reportar sobre las hierbas etnobotánicas más predominantes cultivadas en los patios de una aldea Maya Q’eqchi’ es el de valorizar las capacidades de las tradiciones farmacológicas. Treinta y una entrevistas en base a “caminatas botánicas” y la observación participante informan esta investigación con los residentes de la aldea. Cymbopogon winterianus (para la tos, fiebre), Neurolaena lobata (para la diabetes, fiebre, dolor de cabeza, enfermedades gastrointestinales, mal de ojo) y Ruta chalepensis (para el vómito, el llanto y el mal de ojo en niños) son las hierbas medicinales predominantes. Las investigaciones regionales etnomédicas y farmacológicas actuales apoyan mutuamente la eficacia y la factibilidad de estas plantas y sus usos entre los Q’eqchi’. La investigación etnofarmacológica de las medicinas Maya Q’eqchi’ documenta el conocimiento local como base para la conservación e invita al respeto cultural y biomédico de estas como especies terapéuticas destacadas y accesibles.